SÍNTESE E CARACTERIZAÇÃO DE NANOPARTÍCULAS DE CoFe2O4 E POLI(ÁCIDO LÁTICO-CO-GLICÓLICO) CONTENDO VANILINA - Naidek, Naiane (2014)
This study investigated the synthesis of CoFe2O4 nanoparticles, using the method of coprecipitation of ions Fe3+ and Co2+. After synthesis of CoFe2O4, polymeric nanoparticles of poly (lactide-co-glycolide) (PLGA) with vanillin and CoFe2O4 were synthetized using the double emulsion method. To the synthesis of CoFe2O4, were analyzed the temperature, 80°C and 90°C, and stirring speed, 700 and 1400 rpm. The experimental data shows no influence of temperature and stirring speed in the particle size, the minor size obtained was 75 nm and the major size 92 nm by Dynamic Light Scattering (DLS). Investigation of particle size by Transmission Electron Microscopy (TEM) showed lower values, around 15 nm, indicating that the particles of CoFe2O4 found themselves agglomerated. The chemical composition was confirmed by infrared spectroscopy, energy dispersive X-ray, photoacoustic spectroscopy, thermogravimetric analysis and X-ray diffraction. The magnetic susceptibility was evaluated by analyzing the hysteresis curve, indicating that the sample synthesized at 1400 rpm and 90 °C showed the highest value, this being 58.74 emu.g-1. After synthesis of CoFe2O4, polymeric nanoparticles have been produced by fixing the concentrations of vanillin and CoFe2O4 while the amount of PLGA and polyvinyl alcohol (PVA) used were varied. The synthesized polymeric nanoparticles had sizes between 121 and 569 nm and spherical morphology observed by TEM and DLS. By using larger amounts of PLGA, the experimental data indicated that the size of nanoparticle has decreased. The thermal stability was evaluated by thermogravimetric analysis. To evaluate the efficiency of vanillin encapsulation, high performance liquid chromatography was used with method validation, wherein values of up to 82.28% encapsulation were obtained.